PENGARUH SERVICE QUALITY DAN LIFE STYLE TERHADAP KEPUTUSAN PEMBELIAN (STUDI KASUS PADA WARKOP BREWOK DI KABUPATEN TULUNGAGUNG) - Putri, Windi Kristina; Rakhmawati, Dwi Yuli (Jurnal Pendidikan Tata Niaga (JPTN), 2024)
THE INFLUENCE OF LIFE STYLE AND SERVICE QUALITY ON PURCHASING DECISIONS(Case Study of Warkop Brewok Consumers in Tulungagung Regency) This research aims to determine the magnitude of the influence of life style and service quality on purchasing decisions (case study of warkop beard consumers in Tulungagung Regency. The type of research used is quantitative. The population in this study is warkop beard consumers. The data collection technique uses a questionnaire distributed during June. The sampling technique in this research used a simple random sampling method with a total research sample of 100 consumers. Data analysis used multiple linear regression analysis using the SPSS 26 application. Based on the results of the research and data analysis, it was shown that the life style variables were simultaneous and partial. and service quality has a positive effect on purchasing decisions. Keywords: Life style, service quality, purchasing decisions